Application of logic-probability approach for survivability analysis of security system - Rodin, Sergey (Видавництво Львівської політехніки, 2013)
The article is dedicated to analysys of the survivability of security systems using logical-probability approach. In this paper is described the analysis application and its purpose. The methods and their analogues are noted. The analysis procedure and problems of method were described. The advantages and disadvantages were analyzed.
Keywords: logic-probability; approach; survivability; analysis; security system